Clinical Utility of the Cognitive Test for Severe Dementia: Factor Analysis, Minimal Detectable Change, and Longitudinal Changes - Hiroyuki Tanaka (Dementia and Geriatric Cognitive Disorders Extra, 2018)
Aims: This study sought to conduct additional analyses of the Cognitive Test for Severe Dementia (CTSD) using the COSMIN checklist to ensure the development of adequate outcome measures. Methods: The following analyses were conducted: (1) factor analyses were used to evaluate construct validity; (2) the standard error of measurement (SEM) and minimal detectable change (MDC) were assessed to evaluate reliability and interpretability; and (3) longitudinal change was assessed to evaluate responsiveness. Results: The CTSD factor analysis yielded 2 factors, each of which was dichotomized by the passage rate of each item. We calculated a SEM and MDC of 1.6 and 3.6 points, respectively. Finally, the mean CTSD score showed a significant reduction (p < 0.001) over time, and the change in score exceeded the SEM and MDC. Conclusion: Our results indicate that the CTSD could provide a reliable outcome measure in severe dementia.